The Importance Of Oral Health Care Optimization In Bedridden Medicocompromised Patients: A Case Series - Zahra, Faradina Siti; Parlindungan, Faisal; Aini, Muhammad Hafiz; Wardhany, Indriasti Indah (Faculty of Dentistry, Universitas Islam Sultan Agung, 2025)
Background: Bedridden patients were highly susceptible to oral complications due to prolonged immobilization, impaired oromotor function, and limited capacity for self-care. The accumulation of debris and reduced salivary flow can become pathological, leading to infection in the oral cavity. This case report aims to describe two cases of medico-compromised bedridden inpatient highlighting the importance of optimizing oral health care. Case Report: Two bedridden inpatients were reffered to Oral Medicine Division, Universitas Indonesia hospital from internist. First case, was a 59-year-old female inpatient with stage IV breast carcinoma and bone metastasis. The second case, was a 68-year-old male inpatient with acute encephalopathy and multiple comorbidities. Both patients shows decreased consciousness, severe oral dryness with high Clinical Oral Dryness Scores (CODS), poor oral hygiene with a abundant plaque and debris, inflamed periodontal tissue and lip lesion. Oral health care maintenance by cleaning and wipping teeth and oral mucosa using sterile gauze moistened in 0.9% NaCl was done and demonstrated to caregiver to be done daily. Petroleum Jelly was perscribe for the lips lesions. Both patients showed improved mucosal hydration, debris reduction, and greater comfort. Discussion: Oral cavity infection is one of the factors that plays an important role in accomplishing the successful overall treatment while bedridden patients had increased risks of oral infection due to limited abilities. Cleaning and wipping with 0,9% NaCl was a safe choice for patient with high risk of aspiration, had a mild antiseptic properties and maintain mucosal hydration. Conclusion: Optimization of oral care in bedridden patients begin with the selection of oral health care maintenance methods by considering the patient's systemic condition.